The Bible, social media, and digital culture - Phillips, Peter M. (Routledge, Taylor & Francis Group, 2020)
Bible Engagement in Context -- The Bible, Social Media and Digital Culture -- Lists -- Reflection -- MTD.
Includes bibliographical references and index
Keywords: Bibel; Religiöses Engagement; Social Media; USA; Großbritannien; Day, Abby / 1956-; Davie, Grace; Bible; Social media; Social media / Religious aspects / Christianity; Communication / Religious aspects / Christianity